Virtual Reality and EEG-Based Intelligent Agent in Older Adults With Subjective Cognitive Decline: A Feasibility Study for Effects on Emotion and Cognition - Cuesta, Marc; Verty, Lynn Valeyry; Ben Abdessalem, Hamdi; Byrns, Alexie; Bruneau, Marie-Andrée; Frasson, Claude; Belleville, Sylvie (Frontiers in Virtual Reality, 2022)
Objectives. Immersive virtual reality has tremendous potential to improve cognition in populations with cognitive impairment. We conducted a feasibility and proof of concept study to assess the potential of virtual reality and electroencephalography, with or without an intelligent agent that adapts the presented material to the emotions elicited by the environment. Method. Older adults with subjective cognitive decline recruited from the community received a virtual reality-based intervention taking place in one of two virtual environments, a train (Part 1, N=19) or a music theatre complemented by the intelligent agent (Part 2, N=19). A comparative group (N = 19) was also included who received no intervention. All participants completed measures of affect and cognition before and after the intervention. The group who received interventions completed measures of cybersickness and user experience after the intervention. Results. Participants did not suffer from increased cybersickness following either intervention. They also reported a positive to highly positive user experience in the following dimensions: attractivity, hedonic quality-identity and hedonic quality-stimulation. The measures of affect showed no pre-post change when comparing either intervention to the control condition. However, a reduction of negative affect was observed following the train intervention for participants with a high self-reported negative affect at baseline. Finally, there was a significant improvement in working memory when comparing either intervention groups to the control condition. Conclusion. Our results support the feasibility and tolerability of the technical and preliminary positive results on cognition pave the way for a larger scale randomized clinical trial to confirm efficacy.